Prevalence of Dental Caries in Relation to Dietary Habits and Oral Hygiene in An Outpatient Population of a Dental Hospital - SATHIYAMOORTHY, SHALINI; S, DR. GHEENA.; KUMAR JAIN, DR. RAVINDRA (The journal of contemporary issues in business and government, 2020)
The aim of the study is to determine the prevalence of Dental Caries in relation to dietary habits and oral hygiene in the outpatient population. Dental caries is the most prevalent of Dental diseases. It has a very high morbidity potential that brought this disease to the main focus of the oral health professional. The prevalence of dental caries has long been considered as an important task for the dental health profession. The problem related with dental caries leads to a decrease in the quality of life of the affected individuals. Data was collected from the patients visited Dental college in a time period of June 2019 - March 2020 and calculation was done. The reports included the age group, gender of the patient with ID and name. Records of each case were examined and tabulation was done in excel sheets followed by statistical analysis using SPSS software in IBM. The results was observed as graphs and charts from the data exported to SPSS. From this we obtained that male predilection was more when compared to female (53.6% :46.4%). High caries severity in adults aged 46 - 50 years (22.2%).Within the limitation of the study; high caries severity in adults aged 46-50 years in which was associated with individual characteristics and it is statistically insignificant (p>0.005). Male are affected predominantly more than females.